Links Between Instagram Use and Fear of Missing Out Among Young Adults in Lithuania - Legkauskas, Visvaldas; Žilinskaitė, Ieva (Social Welfare: Interdisciplinary Approach, 2024)
The study involved 247 young adults (155 women and 92 men). The age of the subjects ranged from 18 to 34 years (mean age 22.8 years). 137 respondents indicated that they have secondary education, 86 respondents indicated that they have higher education, 16 respondents higher education and 8 basic education. The study was conducted in the format of an online survey. Two quantitative research tools were used in the quantitative study – The Multidimensional Facebook Intensity Scale (Orosz, Toth-Kiraly, Bothe, 2016), which was adapted to investigate the intensity of Instagram use (Keyte et al., 2020), and the “Fear of Missing Out scale” (Przybylski et al., 2013). The subjects were asked two additional questions assessing the peculiarities of involvement in the Instagram network and socio-demographic questions. The results of the study revealed that women are more likely to use the Instagram network, spend more time in the app, and have a higher expression of FOMO than men. The results of this study also showed that a stronger FOMO was associated with a longer time spent on Instagram among men. Among other things, the more pronounced FOMO is associated with more frequent checks of the Instagram app. Finally, the higher intensity of Instagram use by young adults is associated with a stronger expression of FOMO.